Kepemimpinan Transformasional, Motivasi Kerja dan Performa Kerja Karyawan ; Systematic Literature Review - Hafid Gisen Parastra; Yunia Wardi; Ilham Thaib (IPM2KPE, 2023)
This study aims to analyze the effect of transformational leadership and motivation on employee performance. The research method used is systematic literature review (SLR), which is a systematic review of various articles (literature) related to research variables. The results showed that 15 (75%) studies showed a significant relationship between transformational leadership and work performance, 10 (50%) studies showed a significant relationship between transformational leadership and work motivation, 8 (40%) showed a significant relationship between work motivation and work performance, and 2 (10%) indicate that transformational leadership can influence work performance by mediating work motivation. In conclusion, that transformational leadership influences motivation where the better the implementation of transformational leadership in organizations/institutions/institutions, the more employee motivation increases. Keywords: Transformational Leadership, Work Motivation, Work Performance